Improvement of Ohmic contacts on Ga2O3 through use of ITO-interlayers - Carey, Patrick H.; Yang, Jiancheng; Ren, Fan; Hays, David C.; Pearton, Stephen J.; Kuramata, Akito; Kravchenko, Ivan I. (Journal of vacuum science and technology. B, Nanotechnology & microelectronics, 2017)
The use of ITO interlayers between Ga2O3 and Ti/Au metallization is shown to produce Ohmic contacts after annealing in the range of 500–600 °C. Without the ITO, similar anneals do not lead to linear current–voltage characteristics. Transmission line measurements were used to extract the specific contact resistance of the Au/Ti/ITO/Ga2O3 stacks as a function of annealing temperature. Sheet, specific contact, and transfer resistances all decreased sharply from as-deposited values with annealing. The minimum transfer resistance and specific contact resistance of 0.60 Ω mm and 6.3 × 10−5 Ω cm2 were achieved after 600 °C annealing, respectively. The conduction band offset between ITO and Ga2O3 is 0.32 eV and is consistent with the improved electron transport across the heterointerface.